2018
DOI: 10.1007/s13205-018-1515-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a new exopolysaccharide produced by Halorubrum sp. TBZ112 and evaluation of its anti-proliferative effect on gastric cancer cells

Abstract: In the present study, we aimed to extract, purify, analyze monosaccharide composition of exopolysaccharide (EPS) produced by Halorubrum sp. TBZ112 (KCTC 4203 and IBRC-M 10773) and also to evaluate its possible antiproliferative activity against human gastric cancer (MKN-45) cell line and its biocompatibility effect on normal cells using human dermal fibroblast (HDF) cell line. Average molecular weight and monosaccharide composition were determined by high-pressure size exclusion chromatography (HPSEC) with mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…As the final examples, specific rules about the uterine carcinosarcoma involve multiple parameters, including Natronococcus and Terasakiispira . Both microorganisms are functionally correlated with tumorigenesis ( Angiuoli et al, 2008 ; Hamidi et al, 2019 ). Although the lack of direct connections between such two microorganisms with the uterine carcinosarcoma, their upregulation at least confirms the malignant transformation in candidate tissues, validating our prediction.…”
Section: Discussionmentioning
confidence: 99%
“…As the final examples, specific rules about the uterine carcinosarcoma involve multiple parameters, including Natronococcus and Terasakiispira . Both microorganisms are functionally correlated with tumorigenesis ( Angiuoli et al, 2008 ; Hamidi et al, 2019 ). Although the lack of direct connections between such two microorganisms with the uterine carcinosarcoma, their upregulation at least confirms the malignant transformation in candidate tissues, validating our prediction.…”
Section: Discussionmentioning
confidence: 99%
“…As the existence of sulfate functional groups and the EPSs bioactivities are directly related, the low cytotoxicity potential of the EPSs from Halorubrum sp. TBZ112 was not unexpected [125].…”
Section: Archaeamentioning
confidence: 95%
“…In consistent with our findings, several studies have shown the non-toxic nature of EPSs on different cell line models. 46,49,50 Regarding the no cytotoxicity effect of the EPSs on normal cell line of MDCK, it seems they have biocompatibility features. The biocompatibility is one of the desirable properties of the natural polymers for use in the formulation of food products, medicines and cosmetics.…”
Section: Antiproliferative Activitymentioning
confidence: 99%